UDP-Glucose: A Potential Signaling Molecule in Plants? - Janse van Rensburg, Henry Christopher; Van den Ende, Wim (Frontiers in Plant Science, 2018)
This perspective paper focuses on the most recent results suggesting a potential role for UDP-Glucose as a signaling molecule in plants. In animals, UDP-Glucose is well-established as an extracellular signaling molecule that is sensed by G-protein coupled receptors, activating several downstream defense mechanisms. Recent studies have shown that abnormal growth occurred in both vegetative and reproductive tissue of plants with reduced UDP-Glucose levels, and this could be rescued by exogenous UDP-Glucose. In plants with increased biomass accumulation, the genes involved in UDP-Glucose production were up-regulated. However, excessive endogenous accumulation of UDP-Glucose induced programmed cell death (PCD), and this could also be obtained by exogenous UDP-Glucose application. Plants with decreased UDP-glucose were insensitive to pathogen induced PCD. We speculate that UDP-Glucose acts as an extracellular signaling molecule in plants, and that it may be perceived as a damage-associated molecular pattern.